Analisis Akuisisi Perusahaan Tahun 2019: Studi Kasus Pada PT Holcim Indonesia Tbk oleh PT Semen Indonesia (Persero) Tbk - Giyan Triani Sari; Isni Khoirunnisa; Maharani Dara Dinanti; Endang Kartini Panggiarti (International Forum of Researchers and Lecturers, 2024)
This article was created by reviewing the acquisition case carried out by PT Semen Indonesia of PT Holcim Indonesia. The purpose of writing this article is to determine the impact of the acquisition carried out by PT Semen Indonesia. This research uses the literature review method as a research approach. The information that will be used in this research is optional, obtained not through direct insight, but through the consequences of exploration carried out by experts in the past. The results of this article illustrate that the acquisition occurred when PT Holcim, which is owned by Lafarge Holcim Ltd, clearly stated its hope of being able to sell 80.6% of its portion which was ultimately purchased by PT Semen Indonesia. The conclusion from the discussion of the article is that PT Semen Indonesia's acquisition of PT Holcim Indonesia will result in a decline in the company's financial performance and an increase in company value which occurs due to expanding production limits, increasing products and developing market share at PT Semen Indonesia.